A bifunctional fluorescent probe for sensing of Al3+ and H2S. Issue 18 (22nd April 2021) - Zong, Ziao; Wang, Jing; Bin, Yidong; Wu, Yanliu; Huang, Guimei
Abstract : Compound L was developed from salicylaldoxime and 4-aminobenzamide. L displayed AIE characteristics in the solid state due to a unique dimer formation by intermolecular hydrogen bonds. L could also act as a bifunctional fluorescence probe for Al 3+ and H2 S. Abstract : Al 3+ and H2 S play essential roles in various physiological processes. However, excess Al 3+ and H2 S are harmful to health. Therefore, it is necessary to design a sensitive method for the detection of Al 3+ and H2 S. In this work, compound L was developed based on salicylaldoxime and 4-aminobenzamide. L displayed aggregation-induced emission (AIE) characteristics in the solid state due to a unique dimer formation via intermolecular hydrogen bonds. In addition, L could serve as a multi-responsive fluorescence probe for Al 3+ based on the coordination reaction in a MeOH/H2 O (9/1, v/v, pH = 7.4) medium and for H2 S based on the addition reaction in EtOH/H2 O (7/3, v/v, pH = 7.4) solution. In addition, L showed a fluorescence colorimetric response to Al 3+ in the solid state. Furthermore, L was applied to detect Al 3+ and H2 S in actual water samples.